Enhancing the Understanding about Emotions in Services Interactions - Milan, Gabriel Sperandio (Review of Business Management, 2007)
This article proposes a reflective discussion by means of a theoretical approach about emotion in the context of services. Firstly, emotion is discussed and the role it plays in the interaction existing between customer and front-line personnel of the service provider. Subsequently it treats empowerment and competence of the front-line personnel in maximizing the effects originated from emotion, and, from that, liking, trust and commitment developed between the parties are also discussed. Finally, it is proposed that services rendering companies develop long-term relationships, and in doing so understand in time the value of the customer. Therefore the central objective of the article is to propose a framework that treats the emotion existing in the context of service, and, as a consequence, to identify a few propositions that may contribute for a better understanding of the subject, both in the academic and the entrepreneurial environment. Key-words: Consumer behavior. Emotion. Services interaction. Relationship. Services.